Analysis of the Level of Satisfaction with the Quality of Clinical Services Using the Servqual Method - Ibrahim, Ali; Fitriani, Lesa; Ruskan, Endang Lestari; Sevtiyuni, Putri Eka; Suarli, Pacu Putra (Universitas Medan Area, 2024)
The influence of the globalization era has increased the use of health facilities in society. This increase requires agencies to provide the best possible service to customers. UPT. The Sriwijaya University Health Clinic as one of the providers of health facilities has also experienced the impact of this increase, therefore this agency continues to provide the best service and makes improvements in the services provided so that service users can feel satisfied. The aim of this research is to determine the level of student satisfaction with services at UPT. Sriwijaya University Health Clinic and which dimensions of service quality have a dominant influence on student satisfaction levels. This research involved 117 respondents from all students and was distributed via Google form with a quantitative research type and survey approach. Data analysis techniques were carried out using SPSS 26 and calculations were carried out using the servqual method. The research results show that from the total, the level of student satisfaction is at a percentage of 87% in the very satisfied category and the quality dimension that has a dominant influence is the reliability dimension with a Gap value of -1.17. With Cartesian diagram analysis, the question instruments included in quadrant I and quadrant II have the opportunity to be improved and maintained in quality so that they can get better responses in the future. With this research, it can be taken into consideration by UPT. Sriwijaya University Health Clinic to improve the quality of services provided in every dimension, especially those included in the important category and maintain the quality of services that previously received a good response